Examining the relationship between social media addiction and basic psychological needs in university students during covid-19 restrictions - Bozkurt, İlhan and Bozkurt, Öznur (Journal of Dependence, 2022)
Objective: The aim of this study was to examine the relationship between the level of social media addiction of university students and the level of meeting their basic psychological needs during the COVID-19 epidemic process. Method: Relationships between dependent and independent variables were examined in the study. Therefore, quantitative research method was used. Correlational design was preferred while creating the research design. Students who received undergraduate education at a public university formed the universe of the research. A sample of 508 person was created from this universe by the convenience sampling method. For the collection of research data; Sociodemographic Data Form, Social Media Addiction Scale (SMAS-SF) and University Students Basic Needs Scale (USBNS) were used. Results: Social media addiction and the level of meeting basic psychological needs differ according to sociodemographic variables and social media usage habits. In addition, the participants stated that their use of social media increased during the COVID-19 epidemic process. It was determined that the participants, who stated that the duration of their use of social media increased in this process, showed a significantly higher social media addiction level than the other participants. Conclusion: While some basic psychological needs are not adequately met, the level of social media addiction increases, while meeting them adequately decreases it. Social media usage rates of university students have increased during the epidemic process. In this process, the social media addiction level of those who increased their use of social media was also found to be high.